Transanal minimally invasive surgery for complex rectal adenomas in a regional colorectal unit: early outcomes within a collaborative tertiary network - Keng, Cambo; Thor, Sze Mun; Naseem, Zainab (International Surgery Journal, 2026)
Transanal minimally invasive surgery (TAMIS) is an established technique for local excision of complex rectal adenomas, predominantly performed in tertiary colorectal centres. Access in regional hospitals remains limited. We report our early experience of introducing TAMIS within a regional colorectal unit through structured collaboration with tertiary colorectal services, through a case series of three consecutive patients undergoing TAMIS for complex rectal adenomas in a regional general surgery unit between August and November 2025. One patient underwent staged diagnostic and definitive excision. Lesion size ranged from 25-40 mm and were located in the low to mid rectum. All procedures were completed successfully without conversion. Final histopathology demonstrated tubulovillous adenoma with low-grade dysplasia in all cases. One patient experienced a Clavien-Dindo grade II complication. There were no reoperations or 30-day readmissions. Thus, TAMIS can be safely introduced in selected patients within a regional setting with appropriate multidisciplinary governance and collaborative support. This model enables delivery of organ-preserving surgery closer to home while maintaining safety and appropriate escalation pathways.